Building an effective environmental management science program : final assessment (National Academy Press, 1997)
Assesses the Department of Energy's Environmental Management Science Program - a program that funds basic research related to environmental cleanup of the department's weapons complex. This book also provides recommendations on long-term challenges and opportunities for the program.